2021
DOI: 10.1038/s41598-021-95176-3
|View full text |Cite|
|
Sign up to set email alerts
|

Tailored synbiotic powder (functional food) to prevent hyperphosphataemia (kidney disorder)

Abstract: Hyperphosphataemia is treated with phosphate binders, which can cause adverse effects. Spray-dried synbiotic powder (SP) composed of Lactobacillus casei JCM1134 (a phosphate-accumulating organism; PAO) and Aloe vera is potentially a safer alternative for efficient phosphate removal. In this study, a novel strategy was developed; lysine-derivatized deacetylated A. vera (DAVK) was synthesised and fabricated on phosphate-deficient PAO (PDP) for efficient phosphate transfer and then spray-dried with the supernatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Moreover, the synbiotic formulation demonstrated efficient phosphate removal relative to the calcium carbonate from milk and soft drinks. Overall, the synbiotic formulation stands out as the first preference for phosphate removal from phosphate-rich synthetic media (15.7 mg dipotassium monohydrogen phosphate salt/mL) under simulated in vitro conditions [ 71 ].…”
Section: Biological Approach For Ckd and The Associated Hyperphosphat...mentioning
confidence: 99%
“…Moreover, the synbiotic formulation demonstrated efficient phosphate removal relative to the calcium carbonate from milk and soft drinks. Overall, the synbiotic formulation stands out as the first preference for phosphate removal from phosphate-rich synthetic media (15.7 mg dipotassium monohydrogen phosphate salt/mL) under simulated in vitro conditions [ 71 ].…”
Section: Biological Approach For Ckd and The Associated Hyperphosphat...mentioning
confidence: 99%
“…[5] Both in vitro cultures and in vivo experiments illustrated that the excellent phosphate-enrichment capacity of L. casei JCM 1134 in the digestive tract allowed it to present a crucial role in metabolic diseases mediated by phosphate imbalance. [6,7] Notwithstanding, concerns about the possible adverse effects of live probiotic cells in the health therapy of high-risk patients, including bacteremia and pneumonia have driven continued interest in clinical trials using alternative approaches. Increasing evidence has indicated that the primary health-elevating properties of probiotics maybe connected with the nonviable byproducts known as postbiotics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Both in vitro cultures and in vivo experiments illustrated that the excellent phosphate‐enrichment capacity of L. casei JCM 1134 in the digestive tract allowed it to present a crucial role in metabolic diseases mediated by phosphate imbalance. [ 6,7 ]…”
Section: Introductionmentioning
confidence: 99%